O perfil dos estudantes de graduação a distância nas universidades federais da região Centro-Oeste (2014-2020) - Borges, Leila Cristina (2022)
Knowing the characteristics of the profile of the student of distance education is what guides this research, considering that these data will contribute with fundamental elements for the stages of a distance course. In addition, this information favors the elaboration of policies for distance education and also guarantees the socially referenced quality of the courses offered in the modality. Thus, this study seeks to identify the student profile of undergraduate courses offered in the distance mode by federal universities in the Midwest region, from 2014 to 2020. The theoretical contributions that support this study are contributions from authors such as Aretio ( 2001); Moran (2000); Litto (2007); Santos, E. (2007); Formiga (2009; Giolo (2010); Luz (2012); Lima (2014a, 2014b); Dourado, Santos and Moraes (2017); Dourado and Oliveira (2009; Lima and Alonso (2019); Pessatto (2019); Netto, Giraffa and Faria (2010); Nogueira (2013); Bisinoto (2016); Petrovich (2018); Fonseca (2020); Moreira and Schlemmer (2020); Zaros et al. (2022), among others. qualitative research, of an exploratory and descriptive nature, of the documentary and bibliographic type with the use of quantitative data to understand the reality. The research is structured in four chapters: the first is entitled "Profile of students of distance education courses in the period of 2006 -2020: the state of research"; the second, "Concept, History and Policies of distance education for higher education and the offer with social quality"; the third, "Federal Universities of the Midwest and the expansion of distance education in the context of the PNE (2014-2024)"; and the fourth, "The profile of distance undergraduate students at Federal Universities in the Midwest". The results of the analyzes led to the finding of a predominance of a female profile in the distance modality of the courses offered by federal universities in the Center-West region, whose majority of students are aged between 30 and 39 years, are brown, have the state single, comes from a public school and belongs to the less favored social classes.